Lesson Plan Pilot Project for Physical Science. - Mary Ellen Sloane; Denise FitzGerald Quintel; Christy Groves (Issues in Science and Technology Librarianship, 2018)
Many academic librarians are revising their instructional practice to integrate ACRL's Framework for Information Literacy for Higher Education. The authors collaborated with science faculty to develop and pilot lesson plans with learning goals derived from the Framework. We implemented the lesson plans in both lower-division and upper-division science courses. This article describes the development process and includes the full lesson plans. This case study offers suggestions for science librarians in cultivating instructional design skills and integrating information literacy into the curriculum in order to positively impact student success in science disciplines. [ABSTRACT FROM AUTHOR]